A Decisive Role Played By Language in the Arena of Marketing and Advertisement: An Exploration of Ubiquitous Element - Dr. Prema S (Asian Journal of Management, Entrepreneurship and Social Science, 2021)
The country’s economy depends on the business of the nation. It has numerous benefits. It creates several business opportunities in the field of planning, production, selling, marketing, service, advertisement, etc. In the world of business, language efficiency is highly demanded to communicate with potential customers in a more effective way. Better communication leads to the identification of hidden opportunities as well as threats in the world of business. Business is the medium through which the unlimited wants of human beings are satisfied in the means of production, distribution, exchange of goods and services. Advertisement acts as the main engine for the propagation of marketing and the business arena. To attract customers, efficient advertisement is highly demanded. A well said advertisement attracts voluminous customers towards the product or service. This article tries to underpin the importance of language in the world of advertisement— which is in fact the ubiquitous element in this present era of modernization